Dynamically Phototunable and Redox‐Responsive Hybrid Supramolecular Hydrogels for 3D Culture of Chondrocytes. Issue 19 (28th July 2022) - Yang, Weiya; Teng, Lijing; Sun, Xiaomin; Liu, Jia; Huang, Yongrui; Zhao, Qi; Song, Wenjing; Ren, Li
Abstract: Despite the promising application of chondrocyte encapsulated within supramolecular hydrogels to create cartilage‐like tissue, matching the degradation of supramolecular hydrogels with the cartilage matrix is challenging. Here, an appropriate phototunable and redox‐responsive hybrid supramolecular hydrogel are reported through the synergic crosslinking strategy, in which the gelatinization is driven by quadruple hydrogen bonding stabilized by thermo‐triggered hydrophobic interactions of branched hyaluronic acid supramolecular polymer and dynamic disulfide bond. The non‐covalently cross‐linked network endows hydrogel scaffold with unique self‐healed and shear‐thinning behavior, while the dynamic covalent network endows hydrogels with phototunable and redox‐responsive performance. The mechanical performance of hybridized supramolecular hydrogel can be modulated by controlling photoinitiators (PI) or thiol bonds (SH) content. Besides, the gene expression, protein secretion and histological staining results show that the chondrocytes encapsulated within the hybrid supramolecular hydrogels can maintain chondrocyte phenotype and facilitate the secretion of the cartilaginous specific matrix. Thus, the developed hybrid supramolecular hydrogels hold great potential in chondrocyte carrier for chondrogenesis. Abstract : This work develops a phototunable and redox‐responsive hybrid hydrogel through a low‐temperature co‐blending approach. The non‐covalent crosslinking network confers unique self‐healing and shear thinning behavior to the hybrid hydrogel scaffold, while the dynamic covalent network confers phototunable and redox responsive properties. The hybrid gel can promote matrix secretion from encapsulated chondrocytes while enhancing mechanical stability.